No Association between Elevated 2-h Postprandial Blood Glucose Levels and Functional Outcomes of Small-Artery Occlusion in Patients with Diabetes - Liu, Ji; Hou, Dongzhe; Gao, Yuan; Wu, Jialing (Frontiers in Neurology, 2018)
Background: The association between 2-hour postprandial blood glucose level (2hPBG) and functional outcomes in patients with small-artery occlusion (SAO) is poorly understood. We aimed to explore the relationship between 2hPBG levels and functional outcomes in SAO patients with diabetes. Methods: We retrospectively analyzed 174 diabetic patients diagnosed with SAO, and 2hPBG values were classiﬁed into four groups according to quartiles (< 8.90, 8.90 to < 12.16, 12.16 to < 15.14, and ≥ 15.14 mmol/L), or according to clinical glycemic recommendations for adults with diabetes (<10 and ≥10 mmol/L, respectively). The relationship between 2hPBG levels and modified Rankin Scale (mRS) scores was assessed using univariate and multivariate analyses. Results: Among all patients with SAO, there were 139 patients with favorable outcomes and 35 patients with poor outcomes. National Institutes of Health Stroke Scale scores were significantly different according to mRS scores (P < 0.001) in both the univariate and multivariate analyses. The binary logistic regression analyses showed that compared with the lowest quartile (< 8.90 mmol/L), elevated 2hPBG levels (8.90 to < 12.16, 12.16 to < 15.14, and ≥ 15.14 mmol/L) were not associated with mRS scores after adjusting for multiple confounding factors. Compared to patients with 2hPBG levels <10 mmol/L, those with 2hPBG levels ≥10 mmol/L did not have a significant risk of poor outcome after adjusting for confounders. Meanwhile, the negative results appeared in the ordinal logistic regression of 2hPBG levels and 3-month functional outcomes. Conclusions: Elevated 2hPBG levels were not associated with unfavorable functional outcomes 3 months after stroke onset in SAO patients with diabetes.